Marketing Communication Strategy in Tourism Development based on Local Wisdom of Jayapura City Communities - Sulistiani, Indah; Syarifuddin, Syarifuddin (Jurnal The Messenger, 2022)
Introduction: Based on a two-way communication model, effective communication between stakeholders can foster citizen participation in tourism management. Jayapura City's coastal tourism potential must be professionally managed, as evidenced by limited facilities and ineffective promotional strategies. The study aims to examine the community's social, economic, and cultural characteristics and devise an effective marketing communication strategy for developing coastal tourism in Jayapura City.Methods: A qualitative approach utilizing a causal descriptive survey method, also called mixed methods. With Lisrell, the research was analyzed using multiple linear regression and the Structural Equation Model (SEM) model.Findings: The effectiveness of marketing communication in the development of beach tourism in Jayapura City is relatively low in the role of tourism managers and the use of media in tourism promotion. Coastal tourism managers are still dominated by the elderly who are not updated with digital technology. The potential of culture and local wisdom has not been optimized in tourism management. There has been no synergy between interested parties such as government, customary, and community in the application of tourism marketing communication.Originality: Many studies have been conducted on tourism marketing communication strategies, but only a few have studied them from the perspective of tourism development which involves participation and local wisdom of the people in Papua. This study shows that marketing communication strategies are part of the solution, and research on local wisdom and community culture can provide alternative tourism development to improve the welfare of local communities.